HUBUNGAN PENGETAHUAN ORANG TUA TENTANG FAKTOR RISIKO KANKER DENGAN SIKAP PENCEGAHAN KANKER - Nuraini Hakim, Feni Amelia Puspitasari (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2019)
Cancer is a collection of abnormal cells formed by cells that grow continuously, not limited, not coordinated with surrounding tissues, and not physiological functioning (Price & Wilson, 2005 in Nurhidayah, Hendrawati, Mediani, & Adistie, 2016). The case of cancer in children amounted to 4.7% of cancer at all ages. Indonesia is a country with high cancer cases suffered by children. Parents can make preventive efforts by identifying cancer-causing risk factors. Cancer prevention needs to be done to suppress the amount of morbidity and mortality of cancer. Efforts undertaken to prevent cancer by avoiding the risk factors of cancer-triggers. Preliminary study obtained parents ' knowledge about the risk factor of cancer is quite good, but there is no explanation about its relationship with the cancer prevention attitude that parents do to the child. This research aims to determine the relationship between parents ' knowledge and the prevention of cancer in children. The design of this research uses a descriptive cross sectional to figure out the knowledge level of parents on cancer risk factors in children, and its relation to the attitude of cancer prevention in children. The analysis used is using the Chi square test. The results of the univariate study obtained the most level of knowledge of respondents was good, and attitudes towards the prevention of cancer was positive. Results of bivariate analysis obtained there are no relationship between parental knowledge with cancer prevention (pvalue: 0.396; p > 0.05). The recommendation of this research is to keep parents improving their knowledge of cancer in children and applying cancer prevention efforts in daily life.